Stocking the Patent Pool: What Do Firms Offer for Licensing and Why? - Joshi,Amol; Nerkar,Atul; Mallapragada,Girish (Academy of Management Proceedings, 2012)
Licensing out intellectual property (IP) such as patents is an important source of firm profit. However, the managerial logic for determining which IP firms offer for licensing remains underexplored in the management literature. Past research analyzes the downstream purchasing decisions of IP licensees. In contrast, this study uses the concept of patent pools, a type of R&D consortium, to explore the upstream marketing decisions of IP licensors. Drawing on the resource-based view (RBV), we hypothesize and find that an increase in the value of IP significantly increases the likelihood that the IP is offered for licensing through a patent pool, while an increase in the imitability of IP significantly decreases the likelihood that the IP is offered for licensing. Further, we find differential effects for the intrinsic and extrinsic dimensions of value and imitability on the likelihood of IP licensing. Extrinsic imitability of IP negatively moderates the relationship between the value of IP and the likelihood it is offered for licensing through a pool, whereas intrinsic imitability positively moderates this relationship. Our findings extend the RBV by providing empirical evidence for how managers determine and use the value and imitability of a firm’s IP portfolio to justify technology licensing decisions.
Keywords: Strategy & Entrepreneurship